Helping People Help Themselves : Toward a Theory of Autonomy-Compatible Help - Ellerman, David (World Bank, Washington, DC, 2014)
If development is seen basically as autonomous self-development, then there is a subtle paradox in the whole notion of development assistance: How can an outside party ("helper") assist those undertaking autonomous activities (the "doers") without overriding, or undercutting their autonomy? This conundrum is the challenge facing a theory of autonomy-compatible development assistance - that is, helping theory. Starting from a simple model of non-distortionary aid, the author explores several themes of a broader helping theory, and shows how these themes arise in the work of "gurus" in different fields - John Dewey in pedagogy and social philosophy, Douglas McGregor in management theory, Carl Rogers in psychotherapy, Soren Kierkegaard in spiritual counseling, Saul Alinsky in community organizing, Paulo Freire in community education, and Albert Hirschman, and E.F. Schumacher in economic development. That such diverse thinkers in such different fields, arrive at very similar conclusions, increases confidence in the common principles. The points of commonality are summarized as follows: 1) Help must start from the present situation of the doers. 2) Helpers must see the situation through the eyes of the doers. 3) Help cannot be imposed on the doers, as that directly violates their autonomy. 4) Nor can doers receive help as a benevolent gift, as that increases dependency. 5) Doers must be in the driver seat. One major application of helping theory is to the problems of knowledge-based development assistance. The standard approach is that the helper, a knowledge-based development agency, has the "answers", and disseminates them to the doers. This corresponds to the standard teacher-centered pedagogy. The alternative under helping theory is the learner-centered approach. The teacher plays the role of midwife, catalyst, and facilitator, building learning capacity in the learner-doers, so that they can learn from any source, including their own experience. Development assistance is further complicated by the local, or tacit nature of much relevant knowledge. A knowledge-based development agency might function better, not simply as a source of knowledge, but as a broker connecting those who face problems with those in similar situations, who have learned to address the problems. Changing to the approach of helping theory, entails changing the helping agency itself, transforming it into an organization that fosters learning internally, as well as externally - as in a university, where professors engage in learning, and foster learning in students, but the organization does not adopt official views on the complex questions of the day. This means fostering competition in the marketplace of ideas within the organization, and taking a more Socratic stance with clients, who will then have to take responsibility for, and have ownership of their decisions.